2014
DOI: 10.1039/c4tb01066c
|View full text |Cite
|
Sign up to set email alerts
|

Hollow hierarchical hydroxyapatite/Au/polyelectrolyte hybrid microparticles for multi-responsive drug delivery

Abstract: Hollow hierarchical hydroxyapatite/Au/polyelectrolyte hybrid microparticles with a hollow HAP core and polymer multilayer/Au nanoparticle shell for multi-responsive drug delivery have been prepared via an LbL technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 41 publications
(64 reference statements)
2
30
0
Order By: Relevance
“…A popular and productive approach to multi­responsive materials is to integrate different reactive moieties into individual polymer chains, often taking advantage of controlled and living polymerization techniques . Films prepared by the LbL technique can also respond to multiple stimuli, such as polymer/clay LbL films, polymer/gold nanoparticles multilayers, composites of poly(ethylene glycol)‐functionalized nanoparticles and photochromic polymers, and capsules comprising star polyelectrolytes . This communication describes several examples of an approach to designing multiresponsive LbL films that relies on compartmentalizing chemistry in stratified polyelectrolyte multilayer (PEM) films such that different external stimuli perform different functions.…”
Section: Methodssupporting
confidence: 86%
“…A popular and productive approach to multi­responsive materials is to integrate different reactive moieties into individual polymer chains, often taking advantage of controlled and living polymerization techniques . Films prepared by the LbL technique can also respond to multiple stimuli, such as polymer/clay LbL films, polymer/gold nanoparticles multilayers, composites of poly(ethylene glycol)‐functionalized nanoparticles and photochromic polymers, and capsules comprising star polyelectrolytes . This communication describes several examples of an approach to designing multiresponsive LbL films that relies on compartmentalizing chemistry in stratified polyelectrolyte multilayer (PEM) films such that different external stimuli perform different functions.…”
Section: Methodssupporting
confidence: 86%
“…The generation mechanism of pseudocapacitance performance by N‐5 and N‐6 can be described as follows according to the possible following faradic reactions [Eqs. (6) and ]: true*CH-NH2+2OH-*normalC=NH+2H2normalO+2e- true*normalC-NH2+2OH-*normalC-NHOH+normalH2normalO+2e- …”
Section: Resultsmentioning
confidence: 99%
“…It could be found that the surface of MnCO 3 microparticles was very coarse. [35][36][37] It should also be noted that the total released DOX amount were relatively low for all studied pH conditions. Prior to laser irradiation, the microcapsules were spherical in solution but resembled deflated balloons after being dried for microscopic analysis [ Figure 3( microparticles, indicating the incorporation of polyelectrolyte multilayers around the MnCO 3 template.…”
Section: Aggregation Of Au Nanoparticlesmentioning
confidence: 83%